Successful Outcome in Posttraumatic Superficial Femoral Artery Pseudoaneurysm following Distal Femur Fracture - Lalith Mohan; Sai Charan Vemulapalli; Chandrasekhar Patnala; Asif Hussain Khazi Syed; K. K. Kiran Kumar; A. Sundeep Kund (Journal of Orthopedics, Traumatology and Rehabilitation)
A 60-year-old woman sustained right femur fracture and presented to us after taking native massage therapy for 6 weeks. Radiographs showed suspected posteromedial soft tissue shadow. Further imaging confirmed a rare pseudoaneurysm of the superficial femoral artery. After vascular surgery consultation, a single-stage procedure was planned. Through medial approach to distal femur, Pseudo aneurysm was haemodynamically isolated, opened and its contents evacuated. Neck of pseudo aneurysm is located and ligated. Distal femur plating (broad DCP) was done through the same exposure. Since traumatic pseudoaneurysms are rare entities, surgeons should have a high degree of suspicion for preoperative identification. It facilitates simultaneous vascular repair and fracture fixation. It avoids two-stage incisions, two incisions, intraoperative or postoperative catastrophe, and medicolegal complications. Hence, we advocate to look out for vascular injury in distal femur fractures at a delayed presentation.